Seed transmissibility of Cucumber mosaic virus in Capsicum species - Arogundade, O.; Balogun, O.S.; Kumar, P. Lava (Informa UK Limited, 2019)
Cucumber mosaic virus (CMV) occurs worldwide and is a harmful pathogen for pepper (Capsicum spp.). Transmission of the virus is normally by insect. The possibility of transmission by seed is less clear. Accessions collected from eight states in Nigeria were evaluated to determine seed transmissibility of CMV in Capsicum species. Ten percent of the accessions were seed infected with CMV. Eight plants from each of 22 accessions were artificially inoculated with sap prepared from CMV-infected pepper plants and seed from resulting fruit from the inoculated plants were extracted, planted, and the resulting seedlings tested after 8 weeks. The CMV was detected in all four accessions selected randomly from plants that fruited in which accessions NHCrB/09/059, NCr/AA/MAY/09/015, NCr/SA/01/09/050, and NCr/AA/MAY/09/051 had CMV transmission percentage of 73.33%, 66.67%, 66.67%, or 16.67%, respectively. In another experiment, 100 seed of the pepper cvs. Tatase, Rodo, and Sombo extracted from fresh fruit obtained from local markets were randomly selected and sown in a plastic tray. Germinating seed, and developing plants, were maintained in screenhouse and assayed for symptom development. Three young leaf samples were randomly selected from each stand at 7 weeks after planting and subjected to antigen-coated plate enzyme-linked immunosorbent assay (ACP-ELISA). To evaluate the detection capacity of ELISA, and to prove its reliability, a reverse transcription polymerase chain reaction assay was performed for comparison. Natural seed transmission incidence of 57%, 86%, and 71% were determined for cvs. Tatase, Rodo, and Sombo, respectively. This implies that the ability to be transmitted by seed, and the rate of seed transmission of CMV, is cultivar dependent.